2014
DOI: 10.1016/j.nlm.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Stressor controllability modulates fear extinction in humans

Abstract: Traumatic events are proposed to play a role in the development of anxiety disorders, however not all individuals exposed to extreme stress experience a pathological increase in fear. Recent studies in animal models suggest that the degree to which one is able to control an aversive experience is a critical factor determining its behavioral consequences. In this study, we examined whether stressor controllability modulates subsequent conditioned fear expression in humans. Participants were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 40 publications
3
86
0
Order By: Relevance
“…Using a triadic design that included ES, IS and no shock groups, Baratta et al (2007) found that a session of ES in a different context 24 hours after fear conditioning facilitated subsequent extinction learning relative to IS and control groups, and eliminated spontaneous recovery. A similar study in humans found that an ES session a week prior to fear conditioning, extinction and a spontaneous recovery test also enhanced extinction relative to IS and control groups, and eliminated spontaneous recovery (Hartley et al, 2014). Stressor controllability effects have been shown to depend on plasticity within the vmPFC, which facilitates inhibitory control over brainstem nuclei and the amygdala (Maier and Watkins, 2010).…”
Section: Augmenting Extinctionmentioning
confidence: 94%
See 1 more Smart Citation
“…Using a triadic design that included ES, IS and no shock groups, Baratta et al (2007) found that a session of ES in a different context 24 hours after fear conditioning facilitated subsequent extinction learning relative to IS and control groups, and eliminated spontaneous recovery. A similar study in humans found that an ES session a week prior to fear conditioning, extinction and a spontaneous recovery test also enhanced extinction relative to IS and control groups, and eliminated spontaneous recovery (Hartley et al, 2014). Stressor controllability effects have been shown to depend on plasticity within the vmPFC, which facilitates inhibitory control over brainstem nuclei and the amygdala (Maier and Watkins, 2010).…”
Section: Augmenting Extinctionmentioning
confidence: 94%
“…Although on the surface it may seem that active avoidance and escape from fear paradigms could result in protection from extinction in which a new behavior that eliminates the CS or US prevents extinction learning (see Psychological and Cognitive Factors for a description), recent research on stressor controllability suggests a key difference between the augmentation of extinction with active avoidance and the impairment of extinction observed in protection from extinction paradigms is the subjective perception of internal control in eliminating the presentation of the CS or US (Hartley et al, 2014). In active avoidance and stressor controllability the source of eliminating the aversive event is attributed to the learned actions of the animal, whereas in protection from extinction the source is attributed to external circumstances.…”
Section: Augmenting Extinctionmentioning
confidence: 99%
“…However, developments in the field of learned helplessness suggest that the interactions between stress and controllability are crucial for stress regulation . Recent research is starting to provide paradigms to study stress controllability in humans (Bhanji et al, 2016;Hartley et al, 2014).…”
Section: Future Directions and Open Questionsmentioning
confidence: 99%
“…For example, stress exposure (e.g., cold pressor) impairs the extinction (Hartley et al, 2014) of a conditioned galvanic skin response. Moreover, stress exposure prior to retrieval testing impairs the expression of extinction, resulting in a return of conditional responding (Merz et al, 2014;Raio et al, 2014).…”
Section: Stress Effects On Extinction: Human Studiesmentioning
confidence: 99%